Eco e la totalità debole. Soggettività, produzione segnica e ideologia - Desogus, Paolo (L'ospite ingrato, 2021)
The essay intends to examine Umberto Eco’s semiotics in the light of the main trajectories of study the author followed between the 1960s and the 1980s. First, it considers the key-notion of encyclopedia, as the totality of meaning resulting from the material work of human subjects within certain social relations. Afterward, it sets off to analyse how the semiotician discussed and related his research to the various post-modern theories of that epoch, exalting the semiotic field’s partial and fragmentary status, among which the Italian “pensiero debole”. The article closes by laying out a review if Eco’s concept of “eternal fascism”, and its theoretical difficulties.